2018
DOI: 10.1155/2018/6926712
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Muscles of the Fish Nile Tilapia Caused by Zinc Oxide Nanoparticles and Its Modulation by Vitamins C and E

Abstract: The effects of zinc oxide nanoparticles (ZnONPs) on antioxidants in Nile tilapia muscles and the protective role of vitamins C and E were examined. Two hundred males of Nile tilapia were held in aquaria (10 fishes/aquarium). Fishes were divided into 5 groups: 40 fishes in each group; the first group was the control; the 2nd and 3rd groups were exposed to 1 and 2 mg/L of ZnONPs, respectively; and the 4th and 5th group were exposed to 1 and 2 mg/L of ZnONPs and treated with a (500 mg/kg diet) mixture of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 60 publications
5
24
0
2
Order By: Relevance
“…None of the diets enriched with chemically synthesized ZnO nanopowder could augment the GR activity in the liver and gills. Our results coincide with results already reported, which proved that ZnO NPs inhibited SOD, CAT and GPx activities in juvenile carp (Hao and Chen 2012), and in Nile tilapia where SOD, CAT, GPx, GSH and GR activities were declined (Abdelazim et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…None of the diets enriched with chemically synthesized ZnO nanopowder could augment the GR activity in the liver and gills. Our results coincide with results already reported, which proved that ZnO NPs inhibited SOD, CAT and GPx activities in juvenile carp (Hao and Chen 2012), and in Nile tilapia where SOD, CAT, GPx, GSH and GR activities were declined (Abdelazim et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Vit C is a highly effective antioxidant and a free radical scavenger in many metabolic processes [21,22]. Vit C increases the percentage of live, acrosome-intact sperm, and decreases the percentage of abnormal sperm during storage at 5 • C. Vit C prevents membrane lipid oxidation during preparation and thus has protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Zn-containing nanocompounds (such as ZnO NPs) at their toxic effects or doses could raise the concentration of MDA and reduce the GSH contents. Also, they can reduce the activities of antioxidative enzymes, such as SOD, CAT, glutathione reductase (GR), glutathione peroxidase (GPx), and glutathione-S-transferase (GST), which may be used to investigate the toxicity of these compounds in animals [32].…”
Section: Discussionmentioning
confidence: 99%